If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -14 = 6x + 28 Reorder the terms: -14 + 9x = 6x + 28 Reorder the terms: -14 + 9x = 28 + 6x Solving -14 + 9x = 28 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -14 + 9x + -6x = 28 + 6x + -6x Combine like terms: 9x + -6x = 3x -14 + 3x = 28 + 6x + -6x Combine like terms: 6x + -6x = 0 -14 + 3x = 28 + 0 -14 + 3x = 28 Add '14' to each side of the equation. -14 + 14 + 3x = 28 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = 28 + 14 3x = 28 + 14 Combine like terms: 28 + 14 = 42 3x = 42 Divide each side by '3'. x = 14 Simplifying x = 14
| 3x+k=c | | 5=3(3x-4)+2(3x+1) | | a^2b-3ab-10b=0 | | x^2-ax+(a+3)=0 | | 5x+9+3x-5=36 | | -3-2y=-13 | | -7=8x+13 | | x^3-2x^2-25x=0 | | -6x+7-3x=-2 | | 3xX+5=20 | | 4p-2p=20 | | 4(2x-13)+3x=58 | | 5(w-5)-7w=-27 | | 3(4u-2)=-30 | | 3x+18=2x-2 | | f^2-19=-1 | | 4x^5-2x^4+30x^3-15x^2+50x-25=f(x) | | 4(x-2)+2x=28 | | -25=5(2a-1)+2a | | 2(x+5)+(x-3)=16 | | 37+6x=9x-4 | | 17=16a+1 | | -5(5-x)=20 | | 4x-19x=30 | | (16x+14)-9x= | | 1x+8+9x=74-1x | | 3z-2=4 | | -4(-2x+2)=72 | | X/0.8=6 | | 4x-2(x-5)=-9+4x+13 | | 9+2(x-3)=45 | | 4x-2=4x-4+2 |